1995
DOI: 10.1172/jci118195
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of C5a and C5b-9 generation inhibits leukocyte and platelet activation during extracorporeal circulation.

Abstract: Complement activation contributes to the systemic inflammatory response induced by cardiopulmonary bypass. At the cellular level, cardiopulmonary bypass activates leukocytes and platelets; however the contribution of early (C3a) versus late (C5a, soluble C5b-9) complement components to this activation is unclear. We used a model of simulated extracorporeal circulation that activates complement (C3a, C5a, and C5b-9 formation), platelets (increased percentages of P-selectin-positive platelets and leukocyte-plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(129 citation statements)
references
References 71 publications
5
122
1
1
Order By: Relevance
“…[13][14][15][16] It was notable that, despite increased C3a and C5a release and abundant surface C3 deposition on DAF/Crry-deficient platelets, we observed no P-selectin or activated ␣IIb␤3 integrin expression on these platelets, suggesting that they did not have an activated phenotype. Neutralization of CD59a and CD59b on DAF/Crrydeficient platelets with blocking mAbs during in vitro complement activation assays moderately increased surface MAC staining (data not shown) but likewise did not induce P-selectin or activated ␣IIb␤3 integrin expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] It was notable that, despite increased C3a and C5a release and abundant surface C3 deposition on DAF/Crry-deficient platelets, we observed no P-selectin or activated ␣IIb␤3 integrin expression on these platelets, suggesting that they did not have an activated phenotype. Neutralization of CD59a and CD59b on DAF/Crrydeficient platelets with blocking mAbs during in vitro complement activation assays moderately increased surface MAC staining (data not shown) but likewise did not induce P-selectin or activated ␣IIb␤3 integrin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that complement anaphylatoxins C3a and C5a and the membrane attack complex stimulated degranulation and activation of human and animal platelets. [13][14][15][16] To evaluate the physiologic role of membrane complement regulators on platelets, we studied the fate of murine platelets that are deficient in DAF and Crry with the use of an adoptive transfer model. We describe here that platelets deficient in DAF and Crry, but not DAF or Crry alone, were rapidly eliminated from the circulation in an alternative pathway complement-and nonsplenic macrophagedependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CD55 and CD59 may further modulate complement activation on PMP. CD55 disassembles C3 and C5 convertases (31), whereas CD59 prevents the formation of the terminal complement complex (C5b-9), which can contribute to platelet and endothelial cell activation at sublytic concentrations [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The plates were incubated for 30 min at room temperature. Erythrocyte preparation and hemolytic assays were then performed as described (18).…”
Section: Methodsmentioning
confidence: 99%